Physical and chemical properties of three wild almond wood species grown in Zagros forests - Leila Fathi; Redžo Hasanagić; Yaghoob Iranmanesh; Mohammad Dahmardeh Ghalehno; Miha Humar; Mohsen Bahmani (Les)
In this study, the physical properties (oven-dry density, basic density, volumetric shrinkage, and swelling) and structural components (cellulose, lignin, and extractives content) of three wild almond wood species from southwestern Iran, namely Amygdalus arabica, Amygdalus eburna, and Amygdalus scoparia, were investigated. Wild almond is a valuable wood species in the Zagros forests of Iran, but there is a lack of data on their wood properties. Three adult trees of each species were chosen, and samples were prepared from the breast height diameter to measure the focal properties. Results of analysis of variance (ANOVA) showed that the wood species had a significant effect on the wood density and volumetric shrinkage. Maximum oven-dry density and volumetric shrinkage of wood were identified in Amygdalus scoparia. The highest and lowest content of structural components were found in Amygdalus scoparia and Amygdalus arabica wood species, respectively. A deep understanding of the almond wood characteristics will provide a fresh insight into the relationship between the properties and conservation of these special, as well as applications of their wood.